Robust generation of half-metallic transport and pure spin current with photogalvanic effect in zigzag silicene nanoribbons. (9th September 2019) - Jiang, Peng; Kang, Lili; Tao, Xixi; Cao, Ning; Hao, Hua; Zheng, Xiaohong; Zhang, Lei; Zeng, Zhi
Abstract: Using first-principles density functional theory combined with non-equilibrium Green's function method, we investigate the spin-dependent current generated by photogalvanic effect (PGE) in photoelectric devices based on zigzag silicence nanoribbons with unsymmetrical sp 2 – sp 3 hydrogen passivated edges (H-2H ZSiNRs) and C s symmetry. Due to their unique atomic structures and spin-semiconductor properties, we find that the flow direction of different spin channels, spin polarization and magnitude of the photocurrent can be efficiently controlled by tuning the photon energy ( ) or polarization/helicity angle ( ) of the incident polarized light. Interestingly, at certain polarization/helicity angles or certain photon energy, 100% spin polarized current can be achieved by either linearly or elliptically polarized light. Further, robust pure spin current without an accompanying charge current can be achieved by the irradiation of linearly and elliptically polarized light when the two leads are in antiparallel magnetic configuration and, and . Most importantly, without suffering from Schottky barriers or tunnel barriers at metal-semiconductor interfaces, the generated pure spin current or fully spin polarized current in such a purely two-dimensional device with PGE is several orders of magnitude larger than those achieved in metal/semiconductor/metal structures. These numerical results suggest that the asymmetrically sp 2 – sp 3 terminated ZSiNRs are promising materials for construction of novel photoinduced pure spin current and fully spin polarized current generators, which will be of great significance in future spintronic applications.